China : The stealth empire : why the world is not chinese, yet - Burman, Edward ([S.l.] : Sutton Publishing Ltd, 2008)
The book asks why it is that China despite its size and once advanced culture and technology did not become a world power centuries ago? Burman traces the answer through Chinese innate sense of superiority which made foreign conquest and trade an irrelevance. This is about to change with the evolution of what is termed the Stealth Empire characterised by world dominance in the production of consumer goods, a growing share of world manufacturing and a strong sense of nationalism. The Chinese believe that they need to do nothing as they evolve by the middle of the century into the dominant world power. Burman's book opens a window onto this history and growing sense of national destiny. It will be essential reading for anyone wanting to understand what is going on in the Stealth Empire.
Keywords: China; Economic history; Forecasting; International relations; Political science